2014
DOI: 10.1038/nrm3810
|View full text |Cite|
|
Sign up to set email alerts
|

The amyloid state and its association with protein misfolding diseases

Abstract: The phenomenon of protein aggregation and amyloid formation has become the subject of rapidly increasing research activities across a wide range of scientific disciplines. Such activities have been stimulated by the association of amyloid deposition with a range of debilitating medical disorders, from Alzheimer's disease to type II diabetes, many of which are major threats to human health and welfare in the modern world. It has become clear, however, that the ability to form the amyloid state is more general t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

24
2,056
0
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 2,028 publications
(2,155 citation statements)
references
References 178 publications
24
2,056
0
18
Order By: Relevance
“…The conversion of soluble proteins into fibrillar amyloid deposits is a hallmark of a range of increasingly prevalent neurodegenerative disorders including Alzheimer's Disease (AD) and Parkinson Disease (PD) 1, 2, 3, 4. It has been reported that the species formed during the aggregation reactions have a toxic effect on cells 5, 6, 7, 8.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The conversion of soluble proteins into fibrillar amyloid deposits is a hallmark of a range of increasingly prevalent neurodegenerative disorders including Alzheimer's Disease (AD) and Parkinson Disease (PD) 1, 2, 3, 4. It has been reported that the species formed during the aggregation reactions have a toxic effect on cells 5, 6, 7, 8.…”
mentioning
confidence: 99%
“…It has been reported that the species formed during the aggregation reactions have a toxic effect on cells 5, 6, 7, 8. Several possible mechanisms of cellular damage have been identified with relative contributions that depend on both the concentrations and the types of aggregates present 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11. The aggregation process that results in the formation of oligomers may contribute to cellular damage 12, 13, 14, 15.…”
mentioning
confidence: 99%
See 3 more Smart Citations